Design and comparison of two advanced core control systems for flexible operation of pressurized water reactors. (June 2022) - Dupré, Guillaume; Chevrel, Philippe; Yagoubi, Mohamed; Grossetête, Alain
Abstract: This paper focuses on the design of advanced core control systems for future generations of pressurized water reactors. The objective is to improve the flexibility of nuclear power plants to cope with the rapid growth of renewable energies. In practice, this means that the average coolant temperature, the axial power distribution of the reactor core and the position of the control rods have to be properly regulated during power variations. In previous work, conducted by the same authors, two promising approaches were investigated: 1) fixed-structure gain-scheduled control and 2) nonlinear model predictive control. Here, both methods are tested according to industry standards in an attempt to determine the best one for our problem. To achieve this, two different controllers are designed using a new multipoint kinetic model of the reactor core, which provides an accurate representation of the axial power distribution. The advantages and drawbacks of both design methodologies are discussed and then compared on PWRSimu, an intermediate complexity pressurized water reactor simulator developed by Framatome. Highlights: Current nuclear reactor core control systems still rely on SISO PID technology. A new multipoint reactor core model is presented and used for controller design. Two advanced MIMO controllers are designed and compared against industry standards. Several useful methodological guidelines and practical insights are given in detail. Both controllers are able to meet the real technical specifications of Framatome.